2014
DOI: 10.1016/j.quascirev.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

A community-based geological reconstruction of Antarctic Ice Sheet deglaciation since the Last Glacial Maximum

Abstract: Bentley, M. J., Ocofaigh, C., Anderson, J. B., Conway, H., Davies, B., Graham, A. G. C., Hillenbrand, C. D., Hodgson, D. A., Jamieson, S. S. R., Larter, R. D., Mackintosh, A., Smith, J. A., Verleyen, E., Ackert, R. P., Bart, P. J., Berg, S., Brunstein, D., Canals, M., Colhoun, E. A., Crosta, X., Dickens, W. A., Domack, E., Dowdeswell, J. A., Dunbar, R., Ehrmann, W., Evans, J., Favier, V., Fink, D., Fogwill, C. J., Glasser, N. F., Gohl, K., Golledge, N. R., Goodwin, I., Gore, D. B., Greenwood, S. L., Hall, B. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
201
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(214 citation statements)
references
References 47 publications
8
201
0
1
Order By: Relevance
“…This affects the sea ice and the ocean around the ice shelves, which in turn affect basal melting. With regard to the LGM experiments, reconstructions of the Antarctic ice sheet have shown that the grounding line would have advanced northward to near the continental shelf break during the LGM (Bentley et al 2014;Abe-Ouchi et al 2015). Using the same model as used in this study but with an enlarged LGM ice sheet extent, Kusahara et al (2015) showed that basal melting during the LGM was greater than under the conditions of the present-day climate.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This affects the sea ice and the ocean around the ice shelves, which in turn affect basal melting. With regard to the LGM experiments, reconstructions of the Antarctic ice sheet have shown that the grounding line would have advanced northward to near the continental shelf break during the LGM (Bentley et al 2014;Abe-Ouchi et al 2015). Using the same model as used in this study but with an enlarged LGM ice sheet extent, Kusahara et al (2015) showed that basal melting during the LGM was greater than under the conditions of the present-day climate.…”
Section: Discussionmentioning
confidence: 72%
“…Recent observations have revealed mass loss of the Antarctic ice sheet and thinning of the ice shelves (Pritchard et al 2009;Velicogna 2009;Pritchard et al 2012). Furthermore, geological surveys have elucidated historical variations in the extent of the Antarctic ice sheet under climatic conditions both warmer and colder than the present, represented by the Last Interglacial period and the Pliocene (Kopp et al 2009;Naish et al 2009;Dutton and Lambeck 2012;Cook et al 2013;Masson-Delmotte et al 2013;Suganuma et al 2014;Dutton et al 2015;Yamane et al 2015;McKay et al 2016) and the Last Glacial Maximum (LGM), respectively (Bentley et al 2014;Abe-Ouchi et al 2015;Peltier et al 2015). Numerical ice sheet models have been used to reconstruct the shapes of ice sheets and to investigate their responses to variations in climate forcing de Boer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment is designed as an increasing load, for example representative of the ceasing motion of the Kamb Ice Stream (Ice Stream C; Retzlaff and Bentley, 1993), West Antarctica. Due to the linearity of the viscoelastic field equations, it is not necessary to calculate separately the equivalent unloading experiment, −σ (tϑ), for example corresponding to the past and present glacier retreat of the Amundsen Sea sector, West Antarctica (Bentley et al, 2014 andRignot et al, 2014, respectively). Among others, the combined inversion of the altimetry, gravity and GPS data (the second REGINA paper, Sasgen et al, 2017a) solves for the magnitude and the sign of the load, allowing for ice advance as well as ice retreat.…”
Section: Load Model Parametersmentioning
confidence: 99%
“…Much progress has been made in reconstructing the ice sheet evolution from geomorphological evidence (Bentley et al, 2014) and inferring the underlying Earth structure from seismic observations Heeszel et al, 2016). However, an independent approach to constraining GIA is to make use of the different sensitivities of the various types of satellite data to recent glacial changes and GIA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The WAIS volume has undergone fl uctuations since the Quaternary, from expansion events, with ice covering local mountains and valleys, to the retraction events with exposure of subglacial topography. Several years of research have produced a large set of geological data constraining Antarctic Ice Sheet history, based on the signifi cant progress of acquisition methods and analysis of terrestrial and marine records of past ice-sheet thickness and extent (RAISED, 2014). Geomorphic/geologic studies can provide evidence of past behavior, e.g.…”
Section: Introductionmentioning
confidence: 99%